2022
DOI: 10.1108/jhom-05-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Lean healthcare applied systematically in a medium-sized medical clinic hospitalization

Abstract: PurposeThe objective of this paper is to propose a systematic application of Lean Healthcare in the hospitalization activity in the medical clinic entry process.Design/methodology/approachThe methodology used is established in three stages: the first aims to map the process in which the focus activity is inserted, using lean tools, as well as integrating the employees involved in the application. The second is the proposal to apply the systematic, together with the employees, using the A3 tool step by step. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Regarding engagement, most HCOs reported active engagement of leaders in LM practices, including high-level management support. 15 , 16 , 29 , 30 , 39 , 50 , 53 , 54 Lastly, leaders of HCOs in this stage commonly used previously achieved results to demonstrate LM’s ability to enhance staff commitment and participation in LM. 15 , 29 , 30 , 50 , 51 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding engagement, most HCOs reported active engagement of leaders in LM practices, including high-level management support. 15 , 16 , 29 , 30 , 39 , 50 , 53 , 54 Lastly, leaders of HCOs in this stage commonly used previously achieved results to demonstrate LM’s ability to enhance staff commitment and participation in LM. 15 , 29 , 30 , 50 , 51 …”
Section: Resultsmentioning
confidence: 99%
“…Most HCOs in this stage reported that their leaders successfully created awareness of CI as a cultural development. 15 , 29 , 30 , 50 , 53 , 54 Additionally, leaders in two-thirds of the HCOs aligned the implementation of LM with the organization’s strategy. 29 , 30 , 50 , 53 , 54 Regarding integration through LM, a significant proportion of leaders in this stage aimed to achieve cross-sectional alignment with LM activities 29 , 39 , 50 , 53 , 54 and involve multiple silos during LM activities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations